Applied family law in Islamic courts : Shari$1 (Ba courts in Gaza /s - Shehada, Nahda Younis; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
Written from an ethnographic perspective, this book investigates the socio-legal aspects of Islamic jurisprudence in Gaza-Palestine. It examines the way judges, lawyers and litigants operate with respect to the law and with each other, particularly given their different positions in the power structure within the court and within society at large. The book aims at elucidating ambivalences in the codified statutes that allow the actors to find practical solutions to their (often) legally unresolved problems and to manipulate the law. The book demonstrates that present-day judges are not only confronted with novel questions they have to find an answer to, but, perhaps more importantly, they are confronted with contradictions between the letter of codified law and their own notions of justice. The author reminds us that these notions of justice should not be set a priori; they are socially constructed in particular time and space.
chapter 1 Introduction / Nahda Shehada -- chapter 2 Islamic jurisprudence now and in the past / Nahda Shehada -- t
Keywords: Domestic relations (Islamic law); Domestic relations (Islamic law) -- Gaza Strip; Domestic relations courts -- Gaza Strip; Domestic relations courts; Islamic courts -- Gaza Strip; Islamic courts; LAW / Administrative Law & Regulatory Practice; LAW / Courts; LAW / Family Law / General